A Review on Diesel Soot Emission, its Effect and Control - Ram Prasad; Venkateswara Rao Bella (Masyarakat Katalis Indonesia - Indonesian Catalyst Society (MKICS), 2010)
The diesel engines are energy efficient, but their particulate (soot) emissions are responsible of severe environmental and health problems. This review provides a survey on published information regarding diesel soot emission, its adverse effects on the human health, environment, vegetations, climate, etc. The legislations to limit diesel emissions and ways to minimize soot emission are also summarized. Soot particles are suspected to the development of cancer; cardiovascular and respiratory health effects; pollution of air, water, and soil; impact agriculture productivity, soiling of buildings; reductions in visibility; and global climate change. The review covers important recent developments on technologies for control of particulate matter (PM); diesel particulate filters (DPFs), summarizing new filter and catalyst materials and DPM measurement. DPF technology is in a state of optimization and cost reduction. New DPF regeneration strategies (active, passive and plasma-assisted regenerations) as well as the new learning on the fundamentals of soot/catalyst interaction are described. Recent developments in diesel oxidation catalysts (DOC) are also summarized showing potential issues with advanced combustion strategies, important interactions on NO2 formation, and new formulations for durability. Finally, systematic compilation of the concerned newer literature on catalytic oxidation of soot in a well conceivable tabular form is given. A total of 156 references are cited. © 2010 by Authors, Published by BCREC Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0)